Die wichtigsten Aspekte der interkulturellen Kommunikation beim Fremdsprachenlernen (Journal of Science-Innovative Research in Uzbekistan, 2024)
Effective intercultural communication is crucial in today's globalized world. This article explores the key aspects of intercultural communication in foreign language learning, encompassing cultural awareness, nonverbal communication, active listening, empathy, patience, and intercultural competence.